Improved adherence to statins following pictorial intervention. Sub study of visualization of subclinical atherosclerotic disease for optimum cardiovascular prevention (VIPVIZA). (3rd October 2022) - Holmberg, H; Carlberg, B; Sjolander, M; Glader, E L; Naslund, U; Norberg, M; Sjalander, A
Abstract: Introduction: VIPVIZA is a prospective, randomised controlled trial with open label and masked evaluators, integrated in Västerbotten intervention programme (VIP), a population-based CVD screening and prevention programme examining 40, 50, 60-year-olds. In VIPVIZA subclinical atherosclerosis was identified by ultrasound and pictorial information about carotid plaque presence, carotid thickness and risk assessment was provided to participants and their physicians. After examination, participants were randomized to pictorial information (intervention) or as usual care (control). Previous studies from VIPVIZA have shown that the time to initiation of statins is lower and the proportion of statin users is higher in the intervention group. Purpose: To study whether the pictorial risk information intervention made participants with pre intervention prescription of statins more adherent to statin treatment. Method: During 2013–2016, 3532 participants in VIPVIZA were screened by carotid ultrasound examination, of which 46% had plaque, 546 had expedited prescriptions of statins (ATC codes: C10AAxx, C10B, C10BA, C10BX) prior to inclusion. Participants were followed from inclusion until 3-year follow-up examination. Adherence calculations were based on Swedish prescription drug registry (PDR). For adherence calculations we assumed that medication is used as prescribed. Dose change of same medication is considered, and number of days' supply is recalculated if a dispensing event contains a change of dose. The new dose comes into effect the day of dispensing a prescription with a dose change. For the follow-up period the number of days with potential use (based on supply) is divided by days from baseline examination until 3-year examination, yielding a value in the interval [0, 1] where 0 is non adherent and 1 perfect adherence. Remaining supply of medication at the end of follow-up period is disregarded. Adherence was also dichotomised at 0.8. Results: The average adherence to statins was higher in the intervention group for participants with carotid plaque, 0.844 vs 0.773, confidence interval 95% for mean difference (−0.125, −0.018), p=0.009. The intervention group with carotid plaque had the best adherence of all subgroups, but the difference in adherence within the intervention group (plaque vs no plaque) was non-significant. With respect to sex the difference in mean adherence between intervention and control for males was 0.826–0.795 while for females 0.815–0.742. With dichotomised adherence the increase in the intervention group is significant for females, p=0.027. See table 1. Conclusion: Providing information about subclinical atherosclerosis increases adherence to statins, especially in participants with plaque and females. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swedish Research Council